EVALUATION OF LOCATION AND EXTENT ACCORDING TO ACP CLASSIFICATION FOR PATIENTS UNDERGOING FIXED PARTIAL DENTURE TREATMENT - A RETROSPECTIVE STUDY - Reddy, M. Sai Teja; Ahmed, Nabeel; Sasanka, Keerthi (International Journal of Psychosocial Rehabilitation, 2019)
The aim of this study was to retrospectively evaluate the location and extent according to ACP classification. A total of 786 data entries were taken after reviewing 86000 patient data, duplicate and missing entries were omitted. So a total of 447 entries were evaluated. The data was collected from patient records in Saveetha Dental College, over a period of one year. The evaluation was based on the technique used by the dental students, to measure . The results of the study were subjected to statistical analysis. Data analysis was done using SPSS software version 23.0. Chi-square test and frequency evaluation was done to evaluate correlation of classes with age and gender of the selected samples shows higher male patients seeking prosthodontic treatment than the female patients. Association between the location of the teeth, age and gender was found to be statistically significant. (p